2018
DOI: 10.18415/ijmmu.v5i4.195
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interpretation of Cultural Values in Babad Banyumas Manuscript as a Means to Understanding Banyumas Society

Abstract: Culture as an abstraction of a dynamic human experience, tends to develop in line with development of the supporting communities. Babad Banyumas as a literary work of traditional history reflects the culture which tends to convey a transformative message, and many of which loaded with social life values of the community at the time which became the underlying guidance and characters of the Banyumas society. This study aims to explore the culture and local values of Banyumas community's social life reflected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…According to Jumriani et al, (2021) & (Marti & Ridiah, 2023)local wisdom stands as a cultural attribute that is distinctly affiliated with a specific geographical region, particular ethnic group, or even an entire nation. It encompasses a repository of knowledge, practices, beliefs, and values that have been nurtured and refined over generations within a particular cultural context (Purwoko, 2016;Khoeriyah et al, 2018).…”
Section: Local Wisdommentioning
confidence: 99%
See 2 more Smart Citations
“…According to Jumriani et al, (2021) & (Marti & Ridiah, 2023)local wisdom stands as a cultural attribute that is distinctly affiliated with a specific geographical region, particular ethnic group, or even an entire nation. It encompasses a repository of knowledge, practices, beliefs, and values that have been nurtured and refined over generations within a particular cultural context (Purwoko, 2016;Khoeriyah et al, 2018).…”
Section: Local Wisdommentioning
confidence: 99%
“…Another research was conducted by (Rachmadani, 2021). This study revealed that the Begalan tradition is a unique cultural practice in Banyumas, Central Java, performed during wedding ceremonies (Khoeriyah et al, 2018). It combines dance, speech, and comedy, accompanied by music.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Banyumas people's character is manifested in the sustaining value in everyday life [42]. The character of Banyumas people can be portrayed in Banyumas chronicles, locally called Babad Banyumas, established through historical presence [43,44]. Based on Banyumas chronicle, the character values of its society are linked to the political (vertical) and social-economic (horizontal) association [44].…”
Section: Banyumas Peoplementioning
confidence: 99%
“…This attitude is as what has been stated by Higgins in Handayani et al [29] that selfawareness is the first step to understand oneself and to determine whether someone needs to change the existing patterns of behavior to be more effective. For this reason, Khoeriyah et al [30] adds that maintaining culture and noble values as manifested in individual character is needed, because through culture and values we gain our personal identity in the midst of multiculturalism. Therefore, Hua [31] adds that studying crosscultural concepts does not mean to understand the cultures of other countries, but it facilitates students to become cross-cultural speakers who are able to accept differences without making conflicts, but still have the awareness to maintain their cultural identity.…”
Section: Student Responses Toward Dressing Mannersmentioning
confidence: 99%